2007
DOI: 10.1262/jrd.18088
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Follicle-Stimulating Hormone and Estradiol on Expressions of Vascular Endothelial Growth Factor (VEGF) 120, VEGF164 and Their Receptors in Bovine Granulosa Cells

Abstract: Abstract. Vascular endothelial growth factor (VEGF) isoforms (VEGF 120 and VEGF 164) secreted by granulosa cells are involved in thecal angiogenesis during follicular development in the bovine ovary. However, whether the transcript of the VEGF120 and VEGF164 isoforms differs during follicular development in the ovary is still unknown. We first examined the gene expression of VEGF120, VEGF164, fms-like tyrosine kinase (Flt-1), and fetal liver kinase (Flk-1) in the granulosa cells (GCs) and theca cells (TCs) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 28 publications
(25 reference statements)
2
40
0
1
Order By: Relevance
“…Exogenous hCG injection in this study might have upregulated VEGF mRNA expression. These data agree with similar observations by several investigators (22)(23)(24) that gonadotropins during the periovulatory period and CL formation regulate VEGF expression. Although other studies have shown VEGF expression by both theca and granulosa layers, we found significant increase only in the thecal layers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Exogenous hCG injection in this study might have upregulated VEGF mRNA expression. These data agree with similar observations by several investigators (22)(23)(24) that gonadotropins during the periovulatory period and CL formation regulate VEGF expression. Although other studies have shown VEGF expression by both theca and granulosa layers, we found significant increase only in the thecal layers.…”
Section: Discussionsupporting
confidence: 93%
“…Goats were randomly assigned for ovarian tissue collection at 0, 4,8,12,24, and 48 h after hormone injections. Ovaries were placed in ice-cold buffered saline solution and transported to the laboratory less than 30 min after collection.…”
Section: Animals and Collection Of Periovulatory Folliclesmentioning
confidence: 99%
“…The primers for TEAD4 were the same as those described by Fujii et al [21]. The β-actin (ACTB) transcript was used as an internal control, and the primer sequences were those described by Shimizu et al [22]. All the primer pairs span exon-exon boundaries.…”
Section: Experiments 4: Effects Of Ethionine On the Expression Of Cellmentioning
confidence: 99%
“…Follicles with high expression of VEGFR-2 exhibit low incidences of apoptosis while, the blockage of receptor inhibits the ability of cells to respond to VEGF endogenously or exogenously present and reduces protection against apoptosis (Greenaway et al, 2004). (Shimizu and Miyamoto, 2007) and is capable of inducing angiogenesis (Schnaper et al, 1996). Estrogen binds with specific estrogen response element present in VEGF gene and thus upregulates VEGF expression (Hyder et al, 2000) in bovine granulosa cells (Garrido et al, 1993).…”
Section: Growth and Development Of Folliclementioning
confidence: 99%
“…However, VEGF isoforms are differently expressed by the hormone. Estrogen causes upregulation of VEGF 164 expression while downregulates VEGF 120 expression in bovine granulosa cells (Shimizu & Miyamoto 2007). …”
Section: Growth and Development Of Folliclementioning
confidence: 99%